2010
DOI: 10.1166/jnn.2010.2057
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Crystal Structure on the Fluorescence Emission of Eu3+:LaOF Nanocrystals

Abstract: Optical transitions of Eu(3+)-doped LaOF nanocrystals with tetragonal and rhombohedral structures were studied experimentally using laser spectroscopic method. Fluorescence emissions from 5D1 and 5D0 of Eu3+ in LaOF nanocrystals were detected by exciting the sample with a 532 nm pulsed laser, and the influence of local symmetry on the fluorescence emission of doped ions was observed. The specific crystalline phase as well as the local symmetry on the fluorescence emission was investigated in both the frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 0 publications
1
12
0
2
Order By: Relevance
“…The delay is measured as a phase shift, which can be used to calculate the decay time. Although frequencydomain measurements are often used in fluorescence spectroscopy of organic molecules, only few studies have been devoted to frequency-domain measurements on europium(III) compounds [752][753][754][755][756].…”
Section: Decay Processes and Lifetimesmentioning
confidence: 99%
“…The delay is measured as a phase shift, which can be used to calculate the decay time. Although frequencydomain measurements are often used in fluorescence spectroscopy of organic molecules, only few studies have been devoted to frequency-domain measurements on europium(III) compounds [752][753][754][755][756].…”
Section: Decay Processes and Lifetimesmentioning
confidence: 99%
“…The forced electric dipole transition from 5 D 0 to 7 F 2 is very sensitive to the local crystal field and site symmetry. Experimental observation showed that the overall fluorescence intensity obtained from Eu 3 + :LaOF nanocrystals with tetragonal crystal structure is about 20 times greater than that observed from those with hexagonal crystal structure [65] (Fig. 3).…”
Section: Enhancement Through Local Interaction Adjustment By Crystal mentioning
confidence: 86%
“…For hexagonal LaOF nanoparticles, the La 3+ ion having C 3V symmetry is directly coordinated with four oxygen ions and four fluorine ions [65]. The corresponding bond lengths are 2.4200Å for four La-F bonds and 2.5800Å for four La-O.…”
Section: Enhancement Through Local Interaction Adjustment By Crystal mentioning
confidence: 99%
“…Ln-doped NCs show unique luminescent properties, such as large anti-Stokes shift, long excited state lifetimes, and narrow luminescence band widths [6,7]. Several strategies have been proposed for improving their luminescence efficiency including the introduction of co-dopant ions/sensitizers, surface modification of nanoparticles (NPs), local symmetry and interaction adjustment [8][9][10][11][12], and other strategies for increasing the luminescence emission efficiency of Ln-doped NCs [2,4,5].…”
Section: Introductionmentioning
confidence: 99%